2021
DOI: 10.3389/fpsyt.2020.616420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Trans-Theoretical Model-Based Health Education Program on the Management of Cognitive Dysfunction in Older Adults With Mild Cognitive Impairment: Study Rationale and Protocol Design for a Randomized Controlled Trial

Abstract: Introduction: Recent studies have confirmed that the management of cognitive dysfunction produces considerable positive effects in individuals with mild cognitive impairment (MCI), however, compliance with participation in various cognitive dysfunction management strategies remains scant in older adults with MCI. Health education programs can improve the level of knowledge of the disease effectively, though it remains unclear as to whether health education programs are sufficient to promote behavior changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In the intervention of health information behavior based on TTM, medical staff understand and evaluate the basic information, health information needs, health information acquisition behavior, and evaluation and utilization of health information of CS patients through questionnaires. Medical staff provide continuous intervention nursing according to patients' state to ensure that patients' selfmanagement ability spiraled up in different behavior stages and changed unhealthy behaviors [21,22]. TTM-based health information and behavior combined with continuous nursing can help patients to establish effective behavior patterns, increase their motivation to change behaviors, and significantly improve their health behaviors, so as to restore their motor function and enhance their daily living ability.…”
Section: Discussionmentioning
confidence: 99%
“…In the intervention of health information behavior based on TTM, medical staff understand and evaluate the basic information, health information needs, health information acquisition behavior, and evaluation and utilization of health information of CS patients through questionnaires. Medical staff provide continuous intervention nursing according to patients' state to ensure that patients' selfmanagement ability spiraled up in different behavior stages and changed unhealthy behaviors [21,22]. TTM-based health information and behavior combined with continuous nursing can help patients to establish effective behavior patterns, increase their motivation to change behaviors, and significantly improve their health behaviors, so as to restore their motor function and enhance their daily living ability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TTM is used to study how to change consumer behavior in using credit cards (Xiao et al, 2004) and investment behavior (Loibl & Hira, 2007). TTM is now widely used as a framework for changing educational behavior (Liu et al, 2021;Sardi et al, 2019). Most recently, TTM has been used to study Islamic financial literacy and financial behavior (Dewi & Ferdian, 2021;Dewi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Mirhosseini also demonstrated the positive role of an online psychoeducational support group in perceived stress ( 25 ). Moreover, a study has shown the positive effect of trans-theoretical model-based health education program on the management of cognitive dysfunction in older adults ( 26 ). Due to the particularity of menopausal women in complex symptoms, psychological characteristics, comprehensive interventions from a multidisciplinary, multimodal approach should be implemented ( 27 ).…”
Section: Introductionmentioning
confidence: 99%